2009
DOI: 10.1007/s00268-009-0164-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of Routine Histopathologic Examination of Three Common Surgical Specimens: Appendix, Gallbladder, and Hemorrhoid

Abstract: The routine histopathology examination of the appendix and gallbladder, particularly in cases of empyema and patient's age over 60 years, is of value for identifying unsuspected conditions requiring further postoperative management. However, routine histopathologic evaluation of the hemorrhoid seems unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 24 publications
(37 reference statements)
1
50
0
6
Order By: Relevance
“…10,11 Other studies advocate routine histological examination of all specimens as the safest approach. 5,12,13 In view of this disagreement in the literature, our study sought to determine the frequency of IGBC in our institution and to establish whether selective histological examination of macroscopically abnormal specimens only would have detected these cancers. Secondary aims were to present the treatment given to patients with IGBC in our institution and to estimate the economic impact of a selective approach to gallbladder histology.…”
mentioning
confidence: 99%
“…10,11 Other studies advocate routine histological examination of all specimens as the safest approach. 5,12,13 In view of this disagreement in the literature, our study sought to determine the frequency of IGBC in our institution and to establish whether selective histological examination of macroscopically abnormal specimens only would have detected these cancers. Secondary aims were to present the treatment given to patients with IGBC in our institution and to estimate the economic impact of a selective approach to gallbladder histology.…”
mentioning
confidence: 99%
“…Akbulut et al, reported unusual histological findings in 54 of 5462 (1%) appendectomy specimens; 37 enterobiasis, 6 carcinoids, 4 mucinous cystadenomas, 2 eosinophilic infiltrations, 2 mucoceles, 2 tuberculosis, and 1 neurogenic hyperplasia [4]. An examination of 4545 appendectomy specimens, performed for acute appendicitis, showed 44 (0.97%) unexpected tumours of appendix including an adenocarcinoma and a primary lymphoma of the appendix [5]. Another series analysed histological reports of 324 appendectomy specimens and reported 8 unexpected lesions [6].…”
mentioning
confidence: 99%
“…5,19 Reports on 'selective pathology' based on perioperative visual macroscopic examination of the gallbladder has been documented for several years. In 1998, Taylor and Huang discussed how routine pathological examination of gallbladder is pointless: they proposed selective evaluation according to macroscopic examination.…”
mentioning
confidence: 99%